2016
DOI: 10.1080/01488376.2015.1109576
|View full text |Cite
|
Sign up to set email alerts
|

Getting Help from 2-1-1: A Statewide Study of Referral Outcomes

Abstract: The 2-1-1 information and referral helpline connects economically vulnerable Americans with needed health and social services in their communities. This longitudinal study followed a random sample of 2-1-1 callers in Missouri (n=1,235) to determine the results of the referrals they received. One month after calling 2-1-1, most remembered receiving (93%), tried contacting (91%) and reached (82%) at least one referral they received. Far fewer (36%) received assistance from the referral, ranging from 17% for hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Consistent with other work on 2-1-1 (Boyum et al, 2016), our findings suggest that a major barrier to implementing solutions for certain types of needs (e.g., childcare) may lie in the availability of helping resources. Findings from this study suggest two broad strategies for action to address the needs of low-income families with children.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with other work on 2-1-1 (Boyum et al, 2016), our findings suggest that a major barrier to implementing solutions for certain types of needs (e.g., childcare) may lie in the availability of helping resources. Findings from this study suggest two broad strategies for action to address the needs of low-income families with children.…”
Section: Discussionsupporting
confidence: 88%
“…Prior work has found that childcare and parenting resources may be especially important for altering these trajectories and affecting multiple domains of parent and child well-being (Annie E. Casey Foundation, 2014; Child Care Aware of America, 2015). Consistent with other work on 2-1-1 (Boyum et al, 2016), our findings suggest that a major barrier to implementing solutions for certain types of needs (e.g., childcare) may lie in the availability of helping resources. Findings from this study suggest two broad strategies for action to address the needs of low-income families with children.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, these results have implications for policy. As programs such as needs navigation are developed and implemented, it is important to acknowledge that availability of resources within a community may be a limiting factor in receiving help (Boyum, Kreuter, McQueen, Thompson, & Greer, 2016). To promote a wide range of positive health-related outcomes, public health practitioners and health professionals should advocate for increased support resources at local, state, and federal levels, as well as increased coordination across sectors.…”
Section: Discussionmentioning
confidence: 99%